THE STATUS OF WOMEN IN THE SOCIOPOLITICAL LIFE OF UZBEKISTAN (1991-2016) - Ismoilova Diyoraoy Khursandjon kizi (Western European Studies, 2025)
This article examines the role and status of women in the socio-political life of the Republic of Uzbekistan from 1991 to 2016. After independence, important legislative foundations were created for ensuring women's rights and involving them in political and public administration. Women began to actively participate in parliament, political parties, local councils, education, healthcare, and entrepreneurship. At the same time, problems hindering gender equality persist in some regions. Based on historical, statistical, and legal analysis, the study highlights changes in the status of women and provides recommendations for their wider involvement in socio-political processes
Keywords: gender equality; political participation; women's rights